Draft Genome Sequence of Clostridium tyrobutyricum Strain UC7086, Isolated from Grana Padano Cheese with Late-Blowing Defect - Bassi, Daniela (American Society for Microbiology, 2013)
Clostridium tyrobutyricum is considered the main agent of late-blowing defect in the production of hard cheese. Here, we described the draft genome sequences and annotation of C. tyrobutyricum strain UC7086, which was isolated from Grana Padano cheese with blowing defect, and C. tyrobutyricum DSM 2637 type strain in a comparative study.